2022
DOI: 10.3934/dsfe.2022011
|View full text |Cite
|
Sign up to set email alerts
|

Text-Based Chatbot in Financial Sector: A Systematic Literature Review

Abstract: <abstract> <p>Text-based chatbots are implemented in the financial sector to enhance the relationship between the customer and services provided by the sector, and also to address external challenges and customer requirements. The chatbot technology in the financial sector serves to examine customers' frequently asked questions and the representation of the process using machine learning. In light of this, this study presents a comprehensive systematic literature review of articles focused on te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The study identi ed challenges in security and suggested ways to reduce security challenges found with chatbots. The authors in [33] stated that chatbots' security and privacy vulnerabilities in the nancial sector must be considered and analysed before the developers do the deployment. Through an analysis of the literature, the researchers identi ed the security issues but did not provide a framework or methodology for identifying the security threats in chatbots.…”
Section: Related Workmentioning
confidence: 99%
“…The study identi ed challenges in security and suggested ways to reduce security challenges found with chatbots. The authors in [33] stated that chatbots' security and privacy vulnerabilities in the nancial sector must be considered and analysed before the developers do the deployment. Through an analysis of the literature, the researchers identi ed the security issues but did not provide a framework or methodology for identifying the security threats in chatbots.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, breast cancer detection and classification [1,2], diabetes detection and prediction [3,4], and brain tumor detection and classification [5,6] are some of the impacts that machine learning techniques have shown in the health sector in the past few years [7]. The agricultural sector [8,9] and financial sector [10] are also sectors that have benefited from machine learning techniques. In recent years, we have seen significant advancements in dermatology as researchers and clinicians try to understand the complexities of various skin conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Chatbots are already a common feature on websites and customer-facing applications across numerous sectors [ 7 ]. This is contributed to the chatbot's ability to provide a wide range of successful interpersonal interactions, easy to use interface, the absence of limitations on time and location, and the advancement of interactive teaching methods [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%